Outcomes of 10, 312 patients treated with everolimus‐eluting bioresorbable scaffolds during daily clinical practice – results from the European Absorb Consortium. Issue 3 (31st August 2021) - Wiebe, Jens; Hofmann, Felix J.; West, Nick; Baumbach, Andreas; Carrie, Didier; Bermudez, Eduardo Pinar; Cayla, Guillaume; Hernandez, Felipe Hernandez; de la Torre Hernandez, Jose M.; Koning, René; Loi, Bruno; Moscarella, Elisabetta; et al.
Abstract: Objectives: To asses mid‐term clinical outcomes of bioresorbable vascular scaffolds (BVS) for the treatment of coronary artery disease in a large‐scale all‐comers population. Background: Several clinical settings are underrepresented in randomized studies investigating BVS against drug‐eluting stents. Whether their results can be translated into the heterogeny patient population seen during daily routine requires further investigation. Methods: The European ABSORB Consortium comprises the following European registries: GABI‐R, ABSORB UK Registry, ABSORB France, BVS RAI Registry, and REPARA BVS Registry, which all prospectively collected patient‐level data regarding outcomes following unrestricted BVS implantation. The primary endpoint of target lesion failure (TLF) includes cardiac death, target‐vessel myocardial infarction (TVMI) and target‐lesion revascularisation (TLR) at 12 months. The incidence of scaffold thrombosis (ST) according to ARC criteria was also assessed. Multivariable analysis was used to adjust for differences in patient and lesion characteristics. Results: A total of 10, 312 patients (mean age 58.4 ± 11.4 y) underwent BVS implantation during routine practice. The 12‐month follow‐up was complete in 95.5% of patients. At 12 months, the primary endpoint of TLF occurred in 3.6%; its components cardiac death, TVMI and TLR were documented in 1.2%, 1.8%, and 2.6%, respectively. The definite/probable ST rate was 1.7%. Absence of predilatation, discontinuation of DAPT and scaffold diameter below 3 mm were independent predictors of ST. Conclusions: The EAC demonstrates reasonable real‐world clinical outcome data after BVS implantation. However, the rate of scaffold thrombosis remains high.